Microstructure and Dynamic Magnetic Properties of Thallium-Based Superconductors - Shaari, Abdul Talib (2002)
Ac susceptibility study is one of the best methods in characterizing bulk superconductors. Four systems (A, B, C and D) of Thallium-based bulk superconductors were analyzed using this method. They were A = (TlO.8SCrO.lS) Sr2 (Ca1-xPrx)CU2O7,B=(Tl0.85Cr0.15)Sr2(Ca1-xNdx)Cu2O7, C=(Tl0.85Cr0.15)Sr2(Ca1-xPrx)Cu2O7,and D=(Tl0.85Cr0.15)Sr2(Sr1-xPrx)Cu2O7. The Temperature dependent ac susceptibility curves and field dependent ac susceptibility curves were obtained using Lake Shore AC Susceptometer Model 7000. The dimensions of each sample were 2mmx2mmxlOmm. Certain ranges of temperatures were identified from temperature dependent ac susceptibility curves for use in plotting the field dependent ac susceptibility curves for each sample. The applied fields (0.1 - 10 Oersted) were not high enough to observe the contributions from intragranular supercurrents. Therefore the data obtained were from the intergranular matrix. Bean's Model is used to explain the dynamic magnetic properties that resulted from the data Tc, Tp and Tcj that were obtained from temperature dependent ac susceptibility curves. 10 was calculated from Tc and Tcj using the Ambegaokar-Baratoff formula and Jc (T) were